Build talking apps : develop voice-first applications for Alexa - Walls, Craig (Pragmatic programmers., 2022)
Voice recognition is here at last. Alexa and other voice assistants have now become widespread and mainstream. Is your app ready for voice interaction? Learn how to develop your own voice applications for Amazon Alexa. Start with techniques for building conversational user interfaces and dialog management. Integrate with existing applications and visual interfaces to complement voice-first applications. The future of human-computer interaction is voice, and we'll help you get ready for it. For decades, voice-enabled computers have only existed in the realm of science fiction. But now the Alexa Skills Kit (ASK) lets you develop your own voice-first applications. Leverage ASK to create engaging and natural user interfaces for your applications, enabling them to listen to users and talk back. You'll see how to use voice and sound as first-class components of user-interface design. We'll start with the essentials of building Alexa voice applications, called skills, including useful tools for creating, testing, and deploying your skills. From there, you can define parameters and dialogs that will prompt users for input in a natural, conversational style. Integrate your Alexa skills with Amazon services and other backend services to create a custom user experience. Discover how to tailor Alexa's voice and language to create more engaging responses and speak in the user's own language. Complement the voice-first experience with visual interfaces for users on screen-based devices. Add options for users to buy upgrades or other products from your application. Once all the pieces are in place, learn how to publish your Alexa skill for everyone to use. Create the future of user interfaces using the Alexa Skills Kit today.